RENDIMENTO ESCOLAR DE ALUNOS PRATICANTE E NÃO PRATICANTE DE ESPORTES (Fiep Bulletin - online, 2020)
It is of utmost importance to practice sports mainly in the school environment, enriching the student with benefits, in motor, cognitive functioning, with the correct method applied, being able to visualize results, such as an excellent school performance. To investigate the relationship of school performance the high school students practicing and not practicing sports. The sample consists of 219 students enrolled in the high school of Christ the King College of Patos-PB, practitioners and non-practitioners of sports. The research sample is characterized as non-probabilistic or by judgment. The instruments used were the students' bimonthly bulletins to collect the grades, as well as the list of sports coaches with the names of the students who practice sports. Data were analyzed using the Statistical Package for Social Sciences (SPSS) program and are presented as mean and standard deviation and as tables and graphs. It was found that students who practiced sports had a general average of 7.94 ± 0.65 and non-practitioners 7.97 ± 0.93. Regarding the female gender, the athletes had a mean of 7.78 ± 0.85 and the non-practitioners 8.18 ± 0.75. Male practitioners averaged 7.99 ± 0.59 and non-practitioners 7.67 ± 1.08. Thus, it could be identified that there was no statistical difference between the averages of students practicing and non-practicing sports, revealing that it may be that sports do not influence school performance
Keywords: Sport. Yield. High school